2017
DOI: 10.1080/02670836.2016.1271966
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behavior of Al9Si0.8Fe alloy with different Mn contents

Abstract: It has been reported that the detrimental effect of Fe on the mechanical properties of Al alloys can be eliminated through the addition of Mn. In this study, we examine the effects of the addition of different Mn contents (0.1, 0.2, 0.4 and 0.7 wt-% of Mn) on the microstructure and mechanical behaviour of Al9Si0.8Fe alloy. It is shown that the presence of up to 0.4 wt-% of Mn changed the platelike morphology of β-Al 5 FeSi into α-Al 15 (Fe,Mn) 3 Si 2 with a Chinese script-like morphology. Mn contents higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…This is confirmed by Al-Si-Fe-Mn phase diagram in Fig. 3 [17,18]. Looking carefully at the EDS spectrum of the point number (2), Fig.…”
Section: Microstructural Evaluationsupporting
confidence: 54%
“…This is confirmed by Al-Si-Fe-Mn phase diagram in Fig. 3 [17,18]. Looking carefully at the EDS spectrum of the point number (2), Fig.…”
Section: Microstructural Evaluationsupporting
confidence: 54%
“…The second point marked (2) in Figure 4 shows the presence of Fe and Mn and Si suggesting that this is a Fe intermetallic with some dissolved Mn. From the literature [33,34], it was reported that Ce could modify the morphology of the α-Al 15 (Fe, Mn) 3 Si 2 phase from large Chinese script-like into small and discrete blocky shape particles. No well-developed Chinese script-like particles could be found in the current study, suggesting that a similar modification occurred in the current study.…”
Section: Microstructural Characteristicsmentioning
confidence: 99%
“…The main reasons of selecting this alloy are its castability, high strength to weight ratio, machinability, and also the possibility of improving the properties with heat treatments. Other than silicon this alloy contains Cu in order to increase strength, Fe to achieve an easy release of the cast parts from the die, and Mn to overcome the detrimental effects of Fe [2][3][4][5]. The silicon level of the A384 alloy is very close to the eutectic point in the Al-Si binary phase diagram which means that the microstructure is consisting of Al-Si eutectic phase with a small amount of α-Al dendrites and different intermetallic phases.…”
Section: Introductionmentioning
confidence: 99%